(untitled) (Research, Society and Development, 2022)
Pharmaceutical assistance in the hospital environment is characterized by the hospital pharmacy, which is a clinical unit, located within the hospital, of technical and administrative assistance, administered by a pharmaceutical professional. The pharmacist is essential in the hospital pharmacy because he is qualified to carry out pharmaceutical care and guide patients regarding the safe and rational use of medicines, and also to evaluate and prevent possible errors with drugs, thus reducing the indiscriminate use of medicines. Thus, the objective of this article is to present the importance of the pharmacist in the hospital pharmacy. For this, an integrative review was carried out, based on electronic journals, articles, dissertations and books, published between 2013 and 2022. It was found that the pharmacist is essential in the hospital field, contributing to patient safety and ensuring rational use of medicines, in addition to managing the hospital pharmacy. Thus, pharmaceutical intervention in the hospital allows for the detection of errors that can cause prolonged treatment of patients, generate greater expenses for the hospital, due to dosage errors or even in the selection of drugs that would adapt, and have a lower degree of side effects. and that they act precisely at the focus of the problem. From the introduction of the pharmacist in clinical practice, two beneficial factors were evidenced, the multidisciplinary follow-up to the clinical picture and the reduction of exacerbated expenses. With pharmaceutical assistance in the hospital field, there is a more effective, safe, quality and rational drug therapy, reducing possible losses.